Стендові випробування автотракторного дизеля 2ч10.5/12 за стандартизованими циклами для визначення ефективності роботи ФТЧ - Вамболь, Сергій Олександрович; Строков, Олександр Петрович; Кондратенко, Олександр Миколайович (НТУ "ХПІ", 2014)
Проведено стендові випробування автотракторного дизеля 2Ч10,5/12, випускна система якого оснащена фільтром твердих частинок, розробленим у відділі ПЕУ ІПМаш НАНУ. Отримано характеристики токсичності відпрацьованих газів цього дизеля шляхом прямих вимірювань та із застосуванням відомої формули перерахунку. При аналізі результатів випробувань до них застосовано стандартизований підхід, що міститься у нормах токсичності автотранспортних засобів Європейської Спілки, які чинні і на території України та Російської Федерації.

Bench tests of the vehicle diesel engine 2Ch10.5/12 with particulate matter filter (DPF) in its exhaust system was provide. The DPF was designed in the Piston plants dept. of the A.N. Podgorny Institute for Mechanical Engineering Problems of the National Academy of Sciences of Ukraine (IPMash of NAS of Ukraine). Achieved the characteristics of emission of pollutants with exhaust gases of that internal combustion engine by direct measurements and by using of famous recalculation formula of prof. I.V. Parsadanov. When the results of tests was analyzing applied the standardized approaches which contained in exhaust emissions standards for vehicles of the European Union which are valid in Ukraine and Russian Federation. Data for evaluation of the woking parameters of the diesel engine, parameters of the toxicity of its exhaust gases and of efficiency indicators of the DPF are obtained by linear regression describing of the data that characterize the work of diesel on the following characteristics: the outside speed, load with rotational speed of the diesel crankshaft of mode with the maximum torque, load with rotational speed of the diesel crankshaft of mode with maximum power, the characteristic of idling
Bench tests of vehicle diesel engine 2Ch10.5/12 in a standardized cycles for defining of effective of operating of DPF
Keywords: екологічна безпека; полютанти; фільтр твердих частинок; енергетичні установки; environmental safety; pollutants; particulate matter filter; power plants; internal combustion engines; emission standards